RECITATION CORRECTION OF THE HIJAIYAH LETTER IN SHORT QURANIC SURAHS BASED ON SPEECH RECOGNITION - Fauzi Iskandar, Ahmad
Learning to read and correct short Quranic surahs by using web application facilities is very necessary for facilitating and understanding the reading of the Qur'an. Checking the correctness of the recitation of short Quranic surahs can be done by the speech recognition process by translating voice data into text data. The text data obtained will then be validated for the correctness of the data model built based on the recorded Qori data. Furthermore, the data model will be developed into a reading correction function that produces correction data in the form of numbers for the accuracy of the reading truth and the location of reading errors. The reading accuracy level is obtained by calculating the similarity of the received data with the model data, and the location of the reading error is also obtained by comparing the previously obtained text data with the model data. The location of the reading error will then be displayed in the form of user interface data in this web application to be studied and used as learning material.